Recurrent intraductal papillary neoplasm of the bile duct due to intraductal dissemination: a case report and literature review - Yuki Nakayama; Takahiro Tomino; Mizuki Ninomiya; Ryosuke Minagawa; Yumi Oshiro; Takuma Izumi; Daisuke Taniguchi; Kosuke Hirose; Yuichiro Kajiwara; Kazuhito Minami; Takashi Nishizaki (Surgical Case Reports, 2021)
Abstract Background Intraductal papillary neoplasm of the bile duct (IPNB) is a subtype of biliary tumor. The 5-year survival rate of patients with IPNB who underwent curative resection is 81%. However, IPNB is known to often recur in other parts of the bile duct. Nevertheless, its mechanism remains poorly understood. Herein, we report the case of a patient with recurrent IPNB, which was considered to be attributed to intraductal dissemination in the common bile duct at 12 months after curative resection. We also made a review of the existing literature. Case presentation A 69-year-old man was referred to our hospital for the evaluation and dilation of an intrahepatic bile duct (IHBD) mass. Computed tomography (CT) findings confirmed a mass in the left hepatic duct. Left trisectionectomy, extrahepatic bile duct resection with biliary reconstruction, and regional lymph node dissection were performed. Intraoperative examination of the resection margin at the common bile duct and posterior segmental branch of the hepatic duct was negative for the presence of malignant cells. Histologically, the tumor showed intraductal papillary growth of the mucinous epithelium and was diagnosed as non-invasive IPNB. It had a papillary structure with atypical epithelial cells lined up along the neoplastic fibrovascular stalks. Immunohistochemically, this was as a gastric-type lesion. At 12 postoperative months, CT revealed a 1.5-cm mass in the lower remnant common bile duct. We performed subtotal stomach-preserving pancreaticoduodenectomy. The tumor exhibited papillary growth and was microscopically and immunohistochemically similar to the first tumor. At approximately 16 months after the patient’s second discharge, CT showed an abdominal mass at the superior mesenteric plexus, which was diagnosed as recurrent IPNB. Chemotherapy is ongoing, and the patient is still alive. In this case, as described in many previous reports, IPNB recurred below the primary lesion in the bile duct. Conclusion Based on our review of previous reports on IPNB recurrence, intraductal dissemination was considered one of the mechanisms underlying recurrence after multicentric development. Considering the high frequency and oncological conversion of recurrence in IPNB, regular follow-up examination is essential to achieve better prognosis in patients with recurrent IPNB.